Abdominal Ultrasound for the Diagnosis of Tuberculosis Among Human Immunodeficiency Virus-Positive Inpatients With World Health Organization Danger Signs. (7th April 2019) - Griesel, Rulan; Cohen, Karen; Mendelson, Marc; Maartens, Gary
Abstract: Background: Studies of the value of abdominal ultrasound for diagnosing human immunodeficiency virus (HIV)-associated tuberculosis have major limitations. Methods: We conducted a prospective study of HIV-positive inpatients with cough and World Health Organization danger signs. The reference standard was positive Mycobacterium tuberculosis culture from any site. Participants had at least 2 sputa and 1 blood specimen sent for mycobacterial cultures. Standardized data capture sheets were used for ultrasound reports. A blinded radiologist interpreted chest radiographs, categorized as "likely", "possible", and "unlikely" for HIV-associated tuberculosis. Results: We enrolled 377 participants: 249 women, median age 35 years, 201 with tuberculosis, and median CD4 count 75 cells/µL. The following abdominal ultrasound findings independently predicted tuberculosis: lymph node long-axis ≥10 mm (adjusted odds ratio [aOR], 4.76; 95% confidence interval [CI], 2.41–9.38), splenic hypoechoic lesions (aOR, 3.45; 95% CI, 1.91–6.24), and abdominal/pleural/pericardial effusions (aOR, 1.95; 95% CI, 1.16–3.29). Presence of ≥1 of these 3 features had a sensitivity of 76.4% (95% CI, 69.8–82.3), a specificity of 68.6% (95% CI, 61.1–75.4), and a c-statistic of 0.784 (95% CI, 0.739–0.830). The sensitivity and specificity of chest radiograph assessed as likely tuberculosis was 55.2% (95% CI, 47.2–62.9) and 83.9% (95% CI, 77.0–89.4), respectively. Conclusions: Three features of tuberculosis on abdominal ultrasound independently predicted tuberculosis with moderate diagnostic performance in seriously ill HIV-positive inpatients. Abdominal ultrasound was more sensitive but less specific than chest radiograph for diagnosing tuberculosis in this patient population.